The Implementation of a Love-Based Curriculum in Fiqh Learning and Its Impact on Students’ Understanding in Islamic Junior High Schools: A Qualitative Study - latifatul fitriah; Ah Haris Fahrudi (Jurnal Multidisiplin Indonesia, 2026)
This study aims to explain how a love-based curriculum is implemented in Fiqh learning and to examine its impact on students’ understanding in Islamic junior high schools. This research is motivated by the dominance of conventional teacher-centered learning approaches, which are less effective in encouraging active student engagement and deep understanding of Fiqh materials. This study employs a qualitative approach with a case study design. The research subjects include the principal, Fiqh teachers, and students. Data were collected through observation, interviews, and documentation. To ensure data validity, the analysis was conducted through data reduction, data display, and conclusion drawing using triangulation techniques. The results show that the implementation of a love-based curriculum is carried out through flexible school policies in responding to government directives, adaptive curriculum implementation according to school conditions, and the integration of social and spiritual values in Fiqh learning practices. The success of implementation is strongly influenced by the role of the principal in providing guidance, training, and mentoring for teachers. This approach is proven to enhance student engagement, deepen conceptual understanding, and foster students’ social and religious character. Therefore, a love-based curriculum can serve as an effective alternative approach in Fiqh learning at Islamic junior high schools.